Effect of Banana Consumption to Reducing Hyperemesis Gravidarum In Pregnant Women - Indah Puspitasari; Anggit Yonika Dewi; Ummi Kulsum (Journal of Epidemiology and Public Health, 2025)
Background: Hyperemesis gravidarum (HG) is a severe form of nausea and vomiting during pregnancy that can lead to dehydration, weight loss, and nutritional deficiencies, posing risks to both maternal and fetal health. Exploring the potential of banana consumption as a natural, accessible intervention may offer a simple dietary strategy to alleviate HG symptoms and improve maternal well-being. This study aimed to determine whether banana comsumption contributes to a decrease in the number of cases of nausea and vomiting experienced by pregnant women. Subjects and Method: This was a quasi experiment conducted at the Mitra Siaga Hospital, Tegal, Central Java, Indonesia, in April-May 2024. A number of 30 pregnant women with hyperemesis gravidarum was selected using purposive sampling. Hyperemesis gravidarum was measured using Pregnancy Unique Quantification of Emesis and Nausea (PUQE) questionnaire. Difference score of hyperemesis gravidarum before and after intervention was examined using t test. Results: The results of the Wilcoxon test before and after consuming bananas with Confidence Interval 95% showed p-value = 0.000, with a significance level of p-value 0.000 < 0.05, which indicates that banana consumption is effective in reducing complaints of nausea and vomiting in hyperemesis gravidarum mothers at Mitra Siaga Hospital, Tegal. The results of the linear regression test of the effect of banana consumption on hyperemesis gravidarum t value = 20.110 > t table and the significance level of p-value 0.000 < 0.05, which indicates that banana consumption has a positive and significant effect on reducing complaints of nausea and vomiting in mothers with hyperemesis gravidarum at Mitra Siaga Hospital, Tegal. Conclusion: Banana consumption can reduce vomiting in pregnant women.